Post a New Question

Math

posted by .

Hello, Having trouble with this one...

Solve the inequality:
(2x-3)(4x)+x^2=>(3x+4)^2

I did 2x-3*4x
9x^2-12x on the left side

on the right side:

9x^2+24x+16

I substracted everything on the right side over to the left and made it => zero

9x^2-12x-9x^2-24x-16=>0

-36x-16=>0

x=<4/-9

I'm not sure if this is right or if I made an error somewhere.

  • Math -

    it is correct.

  • Math -

    THANKS!

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question